Co-digestão de glicerina bruta associada a esterco bovino na produção de biogás - Siqueira, Jessé (2012)
In seeking to reduce dependence on fossil fuels, alternative energy sources and less environmental impact has been widely studied, biofuels. Among them, we highlight the biodiesel and biogas. The increased production of biodiesel to meet with Brazilian legislation, invariably leads to an increase in the supply of a co-product called crude glycerin. With a generation of about 10% of the total volume of biodiesel produced large amounts of glycerin are generated annually, however, the costs for purification of the co-product are high. It is necessary to note its correct disposal, since it has high organic load and its improper disposal could mean major environmental impacts. One way is the biodigestion with other organic waste such as cattle manure. Its high carbon biodegradable can be used in co-digestion with cattle manure as a supplement in the production of biogas. The addition of different concentrations of crude glycerin (2%, 4% and 6% m / m) was used as a supplement in anaerobic digestion co-dairy cattle manure in laboratory batch digesters (3.5 L working volume) . The digesters were operated at mesophilic conditions (30 ° C), with hydraulic retention time (HRT) of 30 days. It was analyzed the total solids (TS), volatile solids (VS) and chemical oxygen demand (COD) to determine the process efficiency in the removal of organic matter and its effect on biogas production. The addition of 4% glycerin resulted in higher production of biogas, about 9307 ml. The COD removal efficiency decreased with addition of glycerin, with the greatest reduction in control treatment, 68%. In other treatments increased by 90% and 118% for treatments Gli4% and Gli6% respectively. The VS reductions for the treatments Gli0%, Gli2% Gli4% and Gli6% were 18.17%, 61.60%, 24.36% and 44.83% for the respective treatments.